A second site occupied by Octopus tetricus at high densities, with notes on their ecology and behavior. Issue 4 (4th July 2017) - Scheel, David; Chancellor, Stephanie; Hing, Martin; Lawrence, Matthew; Linquist, Stefan; Godfrey-Smith, Peter
ABSTRACT: We report wild octopuses ( Octopus tetricus ) living at high density at a rock outcrop, the second such site known. O. tetricus are often observed as solitary individuals, with the species known to exist at similar densities and exhibiting complex social behaviors at only one site other than that described here. The present site was occupied by 10–15 octopuses on eight different days. We recorded frequent interactions, signaling, mating, mate defense, eviction of octopuses from dens, and attempts to exclude individuals from the site. These observations demonstrate that high-density occupation and complex social behaviors are not unique to the earlier described site, which had been affected to some extent by remains of human activity. Behavior at this second site confirms that complex social interactions also occur in association with natural substrate, and suggest that social interactions are more wide spread among octopuses than previously recognized.